2017
DOI: 10.3892/etm.2017.4128
|View full text |Cite
|
Sign up to set email alerts
|

Icariin improves osteoporosis, inhibits the expression of PPARγ, C/EBPα, FABP4 mRNA, N1ICD and jagged1 proteins, and increases Notch2 mRNA in ovariectomized rats

Abstract: Icariin (ICA) is a pharmacologically active flavonoid glycoside that shows promise in the treatment and prevention of osteoporosis (OP). However, the mechanisms underlying the anti-osteoporotic effects of ICA remain largely unclear. The present study used quantitative polymerase chain reaction, western blot and immunohistochemical analysis to examine the effects of ICA on several key targets in the Notch signaling pathway in bone tissue in ovariectomized rats. It was observed that ICA has a pronounced benefici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 42 publications
1
47
0
Order By: Relevance
“…Treatment of 10 -6 M ICA significantly increased ALP activity by the third day of treatment, and ALP activity remained elevated on the seventh day of treatment. These findings correspond to those from a previous study, which showed that ICA stimulated osteogenic differentiation (20) and inhibited adipocyte differentiation of rBMSCs (21).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Treatment of 10 -6 M ICA significantly increased ALP activity by the third day of treatment, and ALP activity remained elevated on the seventh day of treatment. These findings correspond to those from a previous study, which showed that ICA stimulated osteogenic differentiation (20) and inhibited adipocyte differentiation of rBMSCs (21).…”
Section: Discussionsupporting
confidence: 92%
“…Our previous study has shown that ICA can improve osteoporosis via the Notch signaling pathway (21), as well as the MAPK signaling pathway has also been shown to be involved in ICA-mediated osteogenic differentiation (26). In the present study, we use ICI as an ER signaling pathway antagonist, to investigate the correlation between ICA and the ER signaling pathway.…”
Section: Discussionmentioning
confidence: 94%
“…CCAAT/enhancer-binding protein-alpha (C/EBP-α) (Kaestner, Christy, & Lane, 1990;Liu et al, 2017) and peroxisome proliferator-activated receptor-γ (PPAR-γ) (Hu, Tontonoz, & Spiegelman, 1995;Kang et al, 2018;Mueller et al, 2002) are the main transcription factors that induce mesenchymal stem cells to differentiate into adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse calvarial defect model, icariin was transplanted in calcium phosphate cement and resulted in enhanced bone and blood vessel formation [10]. Other in vivo studies have reported significant cartilage repair in mice bearing osteochondral defects, as well as bone formation and antiadipogenic behavior ameliorating osteoporotic status of ovariectomized mice [11,12].…”
Section: Accepted Manuscriptmentioning
confidence: 99%